Exploration of Academic dishonesty amongHigher Education Students Build by Gender Analysis - et. al., Mr. Muthukamatchi M, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In an academic institution, the plagiarism is a major part and important issue among the Graduate students. Plagiarism can be a serious crime and danger afflicting publication of research work worldwide. Similarly, Academic integrity (AI) contraventions of plagiarism also increased nowadays among the students, research scholars and academicians. Due to this reason, this study aims to concentrate to relate Academic Integrity related to plagiarism and the seriousness of these issues. The proposed study reveals about the quantitative and qualitative analysis of Academic Integrity and Plagiarism among the Post Graduate student from various Deemed Universities of Chennai City. This study provides the review on AI and Plagiarism based on the category of gender. It is hoped that the outcomes of this analysis may be wont to perceive the problems of educational dishonesty and the ways of development in Plagiarism developed which supports the scholars so as to scale back its occurrences.